The School Transition of rural elementary school to Urban High School: a theoretical approach - Hurtado Balaguera, Luz Esther; Estupiñán, María Rosa (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The article aims to carry out a theoretical approach to the state of the art around the concept, types and processes of school transition in urban and rural contexts of the world. In this sense, the documentary review was based on the research, classification, processing and analysis of 54 articles from specialized journals in education and psychology, at national and international level, in a period of time between 2002 and 2020. In addition, it included reflections and findings from a book and six thesis studies (two undergraduate monographs, three master’s, and one doctoral thesis). It is important to note that most of the contributions found refer to the problem of educational transition in urban contexts, whereas, there is a limited number of studies that address the tensions present in rural areas, this trend occurs both at the national and international place. Likewise, the research addresses school shift from school and non-school perspectives, such as academic performance, dropout, school coexistence, behavior, self-esteem and the relationships of students with their classmates, parents and teachers.